Opentalk application’s impact towards EFL high school student’s speaking skills - Safitri, Devi Wanda; Anwar, Choiril (Journal of Religion and Linguistics, 2024)
There have been so many applications that can be used to improve students’ language skills, but not many of them have applied Opentalk for improving students’ speaking skills. The purpose of this study is to find out whether using the Opentalk application effective to improve student’s speaking skills of the tenth grade of MAN Kendal in academic year 2022/2023. This study used a quasi-experimental research design that consist of two classes, namely experimental class and control class. The sample was 36 students of X-1 as a control class and 36 students of X-10 as experimental class. The instrument for collecting data in this study was speaking test. The result of this study showed that the pre-test mean score of the control class was 67.11 and that of the experimental class was 60.78. After having treatment, the post-test mean score of control class was 72.11 and that of the experimental class was 65.89. The result of the analysis showed that there was a significant difference. It was supported by the result of t-test that showed sig (2-tailed) 0.004. It could be concluded that H0 was rejected and Ha was accepted meaning that the use of Opentalk application was effective to improve student’s speaking skills.